2005
DOI: 10.1295/polymj.37.439
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analyses of Methyl Bicyclobutane-1-carboxylate Oligomers Formed with tert-Butyllithium/Aluminum Bisphenoxide and Mechanistic Aspect of the Polymerization

Abstract: ABSTRACT:Anionic polymerization of methyl bicyclobutane-1-carboxylate (MBCB) with tert-butyllithium (t-BuLi)/bis(2,6-di-tert-butylphenoxy)ethylaluminum [EtAl(ODBP) 2 ] in toluene at À78 C gives transtactic polymers (trans contents > 90%) with high yields, but with low initiator efficiency and broad molecular weight distribution. In order to obtain information on the initiation mechanism, oligomers of MBCB were prepared with t-BuLi/EtAl-(ODBP) 2 in toluene at À78 C, and fractionated into dimer to pentamer by si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…29 Anionic polymerization of methyl bicyclobutane-1-carboxylate itself gives trans-ratios of >90%, when initiated with tert-butyllithium/bis(2,6-di-tert-butylphenoxy)ethylaluminum in toluene at À78 C, albeit with low initiator efficiency and broad molecular weight distribution. 34 A mechanistic study concluded that attack of tert-butyllithium on the ester to incorporate less-reactive ketone unit anions was occurring as a side-reaction but was mostly suppressed by coordination of the ester to the aluminium Lewis acid. 34 Photochemical methods have been employed for synthesis (and degradation) of BCB, and the mechanistic pathways of these reactions have been studied.…”
Section: Properties and Reactivitymentioning
confidence: 99%
See 2 more Smart Citations
“…29 Anionic polymerization of methyl bicyclobutane-1-carboxylate itself gives trans-ratios of >90%, when initiated with tert-butyllithium/bis(2,6-di-tert-butylphenoxy)ethylaluminum in toluene at À78 C, albeit with low initiator efficiency and broad molecular weight distribution. 34 A mechanistic study concluded that attack of tert-butyllithium on the ester to incorporate less-reactive ketone unit anions was occurring as a side-reaction but was mostly suppressed by coordination of the ester to the aluminium Lewis acid. 34 Photochemical methods have been employed for synthesis (and degradation) of BCB, and the mechanistic pathways of these reactions have been studied.…”
Section: Properties and Reactivitymentioning
confidence: 99%
“…34 A mechanistic study concluded that attack of tert-butyllithium on the ester to incorporate less-reactive ketone unit anions was occurring as a side-reaction but was mostly suppressed by coordination of the ester to the aluminium Lewis acid. 34 Photochemical methods have been employed for synthesis (and degradation) of BCB, and the mechanistic pathways of these reactions have been studied. 37 The 185 nm photolysis of BCB leads to the formation of butadiene and cyclobutene (Scheme 1D).…”
Section: Properties and Reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Many bicyclo[1.1.0]­butanes, however, can be purified by conventional chromatographic methods and stored over prolonged periods of time. This surprising level of chemical inertia originates from the relatively high kinetic barrier for ring-opening processes. , A major general reactivity pattern, especially for bicyclo[1.1.0]­butanes conjugated to electron-deficient groups (e.g., ester, aldehyde, amide), is radical addition, and this property is useful for the preparation of organic polymers. Typically, 1,3-disubstituted and sterically shielded bicyclo[1.1.0]­butanes are more robust than less-substituted analogues, and neat samples can be stored at −20 °C for several months with minimal decomposition. Small amounts of radical inhibitors (e.g., BHT) can provide additional stabilization.…”
Section: Strain Effects In Bicyclo[110]butanesmentioning
confidence: 99%
“…32,33 In recent years, Nakano et al [34][35][36][37] has reported radical, anionic and cationic polymerizations of 2,7-di-npentyldibenzofulvene and dibenzofulvene, which are 1,1-diphenylethylene analogs and yield p-stacked polymers.…”
Section: Polymerizations Of (S)-mpaiimentioning
confidence: 99%